2010
DOI: 10.1007/s11695-010-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Appendix Carcinoid Tumors Among Candidates for Bariatric Surgery: Diagnostic and Therapeutic Implications

Abstract: Although the appendix has been recognized as a preferential site for carcinoid tumors in obese patients, no definitive guidelines are so far available regarding the management of these patients when candidates for bariatric surgery. This study was designed to fill that gap. Between 2000-2008, 558 patients underwent bariatric procedures. Appendectomy was routinely performed in 477 cases. Their charts were retrospectively retrieved and histopathology responses on surgical specimens were recorded. We aimed to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The reported incidence has increased in more recent years [1,6]; however, the overall incidence rate is probably roughly within the same range between different races, although some differences have been reported [1,12,15,16,17,18]. Furthermore, common practice in performing appendicectomies may also influence the reported incidence of appendiceal NEN [19,20]. …”
Section: Epidemiology and Prognosismentioning
confidence: 99%
“…The reported incidence has increased in more recent years [1,6]; however, the overall incidence rate is probably roughly within the same range between different races, although some differences have been reported [1,12,15,16,17,18]. Furthermore, common practice in performing appendicectomies may also influence the reported incidence of appendiceal NEN [19,20]. …”
Section: Epidemiology and Prognosismentioning
confidence: 99%
“…A few case reports have described an incidental finding of NET, most frequently gastric NET, among morbidly obese patients before or after bariatric surgery . One small study showed a high incidence of appendiceal NET among candidates for bariatric surgeries …”
Section: Discussionmentioning
confidence: 99%
“…There are reports of patients with inflammatory bowel disease having a higher incidence of appendix cystadenomas, [12] and bariatric patients having a higher incidence of appendix carcinoid tumours. [13] It is felt that screening is not warranted considering the low incidence of these types of tumours.…”
Section: Discussionmentioning
confidence: 99%